Expanding Export Variety: The Role of Institutional Reforms in Developing Countries - Liugang Sheng; Dennis Tao Yang (Institute for the Study of Labor (IZA), 2013)
This paper presents theory and evidence showing that institutional reforms in developing countries can effectively expand their product varieties in export. Our model demonstrates that relaxing foreign ownership controls and improving contract enforcement can induce multinational companies to produce new products in host developing countries, and that a combination of the two reforms has an amplifying effect on the introduction of product varieties. Consistent with these theoretical predictions, we find empirically that ownership liberalization and judicial quality played an important role in raising the extensive margin of processing exports in China for the period of 1997-2007.
Keywords: D23; F14; L22; 330; export variety; ownership structure; contract environment; processing trade; policy reform; China